2021
DOI: 10.7717/peerj.11659
|View full text |Cite
|
Sign up to set email alerts
|

Particularities of the changes in young swimmers’ body adaptation to the stimuli of physical and mental stress in sports training process

Abstract: Background A factor favoring the swimming performance increase is the adaptation and readaptation of body energetic and functional systems to the physical and mental stress stimuli in training and competitions. The efficiency of monitoring the young swimmers’ training is based on a precise determination of the changes in the specific adaptations. The evaluation and control of the biochemical, mental and motor changes ensure the knowledge of the particularities of body adaptation in different tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…they stated that electronic sports result in psychological and physiological health issues because of its competitive essence and excessive play. In another work, Mihailescu et al (2021) concluded that the glucose and insulin levels of the players rose substantially after an intense workout. La Fratta et al (2021) arrived at the conclusion that their regular exercises are efficient in uric acid, glucose, and some biochemical factors of university students.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…they stated that electronic sports result in psychological and physiological health issues because of its competitive essence and excessive play. In another work, Mihailescu et al (2021) concluded that the glucose and insulin levels of the players rose substantially after an intense workout. La Fratta et al (2021) arrived at the conclusion that their regular exercises are efficient in uric acid, glucose, and some biochemical factors of university students.…”
Section: Resultsmentioning
confidence: 99%
“…To sum up, so as to generate prospective sports psychology training and intervention methods, it seems crucial to detect stress and anxiety in the electronic sports ambiance and its effects on psycho physiological, cognitive, and motor efficiency (Mihailescu et al, 2021). There seems to be a necessity for experimental analyses to advocate the idea that it is related to stress.…”
Section: Introductionmentioning
confidence: 99%